Equatorial wave embedded within the Madden-Julian oscillation leading to the 2021 Peninsular Malaysia flood - Jackson Hian-Wui Chang; Maggie Chel-Gee Ooi; Juneng Liew; Yong Jie Wong; Fuei Pien Chee; Justin Sentian; Putu Aryastana; Jason Pajimola Punay; Neng-Huei Lin (Meteorology and Atmospheric Physics, 2026)

Childhood residential proximity to the radiologically contaminated Coldwater Creek and later-life cardiovascular disease in the St. Louis Baby Tooth study - Michael Leung; Joyce J.Y. Lin; Murray A. Mittleman; Justin G. Farmer; Ian W. Tang; Kaleigh McAlaine; Joseph J. Mangano; Marc G. Weisskopf (Science of The Total Environment, 2026)

Prenatal and early postnatal lead exposure and later adulthood BMI: The Saint Louis baby tooth – Later life health study - Joyce J.Y. Lin; Ruby Hickman; Michael Leung; Justin Farmer; Ian W. Tang; Kaleigh McAlaine; Tracy Punshon; Brian P. Jackson; Felicitas B. Bidlack; Joseph J. Mangano; Marc G. Weisskopf (Environmental Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

Impact of technological innovation on China's mining industry: Perspectives of energy and environmental performance - Runqing Zhu; Zuopeng Justin Zhang; Boqiang Lin (Environmental Impact Assessment Review, 2024)

Changes in plasma concentrations of per- and Polyfluoroalkyl substances after bariatric surgery in adolescents from the Teen-Longitudinal Assessment of Bariatric Surgery (Teen-LABS) study - Brittney O. Baumert; Sandrah P. Eckel; Jesse A. Goodrich; Zhenjiang Li; Nikos Stratakis; Douglas I. Walker; Yinqi Zhao; Fabian Christoph Fischer; Scott Bartell; Damaskini Valvi; Xiangping Lin; Zoe Coates Fuentes; et al. (Science of The Total Environment, 2024)

Spatial relationship between pre-harvest hail and the impact from the wheat streak mosaic disease complex by using remote sensing data - Dongmei Chen; Gary L. Hein; Rebecca Adams-Selin; Lin Wang; Jingcheng Zhang; Xianfeng Zhou; Huiqin Ma; Justin McMechan; Yeyin Shi (Crop Protection, 2024)

Microplastics and cadmium affect invasion success by altering complementarity and selection effects in native community - Feng He; Jianfan Sun; Justin S.H. Wan; Mohsin Nawaz; Qaiser Javed; Linxuan Pan; Wajid Ali Khattak; Yanwen Bo; Yan Xiang; Guangqian Ren; Xin Lin; Daolin Du (Science of The Total Environment, 2024)

Enhanced catalytic activity of H2 heat-treated porous ceria for direct conversion of carbon dioxide into dimethyl carbonate - Zhuxian Yang; Monica Mengdie Lin; Xinhuan Lu; Justin Tay Zheng; Wen-Yueh Yu; Yanqiu Zhu; Hong Chang; Yongde Xia (Chemical Engineering Journal, 2024)

Remediation of diesel-oil contaminated soils using an innovative nanobubble and electrolyzed catalytic system - Wei-Ting Chen; Justin Chun-Te Lin; Shih-Hsiung Chen; Francis Verpoort; Kun-Liang Hong; Rao Y. Surampalli; Chih-Ming Kao (Journal of Cleaner Production, 2023)

Evaluating the synergistic effect of digitalization and industrialization on total factor carbon emission performance - Ruiyang Ma; Zuopeng (Justin) Zhang; Boqiang Lin (Journal of Environmental Management, 2023)

Understanding spatial evolution of global climate change risk: Insights from convergence analysis - Penghu Zhu; Zuopeng (Justin) Zhang; Boqiang Lin (Journal of Cleaner Production, 2023)

Towards carbon neutrality: How much do forest carbon sinks cost in China? - Jiamin Ge; Zuopeng (Justin) Zhang; Boqiang Lin (Environmental Impact Assessment Review, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

A 2019 Outbreak Investigation of Hepatitis A Virus Infections in the United States Linked to Imported Fresh Blackberries - Monica McClure; Johnson Nsubuga; Martha P. Montgomery; Erin Jenkins; Alvin Crosby; Daniela Schoelen; Colin Basler; Sumathi Ramachandran; Yulin Lin; Guo-liang Xia; Yury Khudaykov; Vilasini Suktankar; et al. (Food and Environmental Virology, 2022)

Extended Middle Cerebral Artery Occlusion (MCAO) Model to Mirror Stroke Patients Undergoing Thrombectomy - Sarah J. Messmer; Kathleen E. Salmeron; Jacqueline A. Frank; Christopher J. McLouth; Douglas E. Lukins; Tyler C. Hammond; Ai-Ling Lin; Justin F. Fraser; Keith R. Pennypacker (Translational Stroke Research, 2022)

Pathogen resistance in Sphagneticola trilobata (Singapore daisy): molecular associations and differentially expressed genes in response to disease from a widespread fungus - Shan-Shan Qi; Bharani Manoharan; Vignesh Dhandapani; Sridharan Jegadeesan; Susan Rutherford; Justin S. H. Wan; Ping Huang; Zhi-Cong Dai; Dao-Lin Du (Genetica, 2022)

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Orographic effects on the propagation and rainfall modification associated with the 2007–08 Madden–Julian oscillation (MJO) past the New Guinea Highlands - Yuh-Lang Lin; William Agyakwah; Justin G. Riley; Huang-Hsiung Hsu; Li-Chiang Jiang (Meteorology and Atmospheric Physics, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Allelopathy confers an invasive Wedelia higher resistance to generalist herbivore and pathogen enemies over its native congener - Shan-Shan Qi; Yan-Jie Liu; Zhi-Cong Dai; Ling-Yun Wan; Dao-Lin Du; Rui-Ting Ju; Justin S. H. Wan; Stephen P. Bonser (Oecologia, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A full-scale study of external circulation sludge bed (ECSB) system for anaerobic wastewater treatment in a whiskey distillery - Yu-Chung Lin; Chen-Hua Ni; Chin-Yi Wu; Justin Chun-Te Lin (Environmental Science and Pollution Research, 2019)

Tropical cyclone sensitivities to CO2 doubling: roles of atmospheric resolution, synoptic variability and background climate changes - Gabriel A. Vecchi; Thomas L. Delworth; Hiroyuki Murakami; Seth D. Underwood; Andrew T. Wittenberg; Fanrong Zeng; Wei Zhang; Jane W. Baldwin; Kieran T. Bhatia; William Cooke; Jie He; Sarah B. Kapnick; et al. (Climate Dynamics, 2019)

Perspective: Something Old, Something New? Review of Wasting and Other Mortality in Asteroidea (Echinodermata) - Ian Hewson; Brooke Sullivan; Elliot W. Jackson; Qiang Xu; Hao Long; Chenggang Lin; Eva Marie Quijano Cardé; Justin Seymour; Nachshon Siboni; Matthew R. L. Jones; Mary A. Sewell (Frontiers in Marine Science, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Effects of doping amounts of potassium ferricyanide with titanium dioxide and calcination durations on visible-light degradation of pharmaceuticals - Justin Chun-Te Lin; Mark Daniel G. de Luna; Mary Jane N. Gotostos; Ming-Chun Lu (Environmental Science and Pollution Research, 2016)

Regulation of fibronectin gene expression in cardiac fibroblasts by scleraxis - Rushita A. Bagchi; Justin Lin; Ryan Wang; Michael P. Czubryt (Cell and Tissue Research, 2016)

Older individuals with HIV infection have greater memory deficits than younger individuals - I. Lin Tan; B. R. Smith; Edward Hammond; Heidi Vornbrock-Roosa; Jason Creighton; O. Selnes; Justin C. McArthur; Ned Sacktor (Journal of NeuroVirology, 2013)

Carbon dynamics and community production in the Mississippi River plume - Xianghui Guo; Wei-Jun Cai; Wei-Jen Huang; Yongchen Wang; Feizhou Chen; Michael C. Murrell; Steven E. Lohrenz; Li-Qing Jiang; Minhan Dai; Justin Hartmann; Qi Lin; Randy Culp (Limnology and Oceanography, 2012)
Dissolved inorganic carbon (DIC), total alkalinity (TAlk), pH, and dissolved oxygen (DO) were determined in the Mississippi River plume during five cruises conducted in the spring, summer, and fall. In contrast to many other large rivers, both DIC and TAlk were higher in river water than in seawater. Substantial losses of DIC, relative to TAlk, occurred within the plume, particularly at intermediate salinities. DIC removal was accompanied by high DO, high pH, and nutrient depletion, and was attributed to high phytoplankton production. As a result, the carbonate saturation in the plume became much higher than in ocean and river waters. A mixing model was used to determine DIC removal. We provide evidence that the use of a two—end‐member (river and ocean) mixing model was valid during late summer and fall (low discharge period). However, for other periods we used salinity and TAlk to delineate a mixing model that included two river end members and an ocean end member. Net community production rates in the plume, estimated using a box model, peaked in the summer and were among the highest reported to date for large river plumes. In the summer and fall, biological production in the river plume consumed a majority of the available nutrients, whereas during the spring only a small fraction of the available nutrients were consumed in the plume. Biological production was the dominant process influencing pH and carbonate saturation state along the river—ocean gradient, whereas physicochemical dynamics of mixing played an important role in controlling the TAlk and DIC distributions of this large river plume.

The effect of feed salinity on the biofouling dynamics of seawater desalination - Hui-Ling Yang; Jill R. Pan; Chihpin Huang; Justin Chun-Te Lin (Biofouling, 2011)

Fecundity, brood loss and egg development through embryogenesis of Armases cinereum (Decapoda: Grapsidae) - Joana Figueiredo; Gil Penha-Lopes; Justin Anto; Luís Narciso; Junda Lin (Marine Biology, 2008)

Culture Duration Modulates Collagen Hydrolysate-Induced Tissue Remodeling in Chondrocyte-Seeded Agarose Hydrogels - Kenneth W. Ng; Justin D. Saliman; Evan Y. Lin; Lauren Y. Statman; Lindsay E. Kugler; Sean B. Lo; Gerard A. Ateshian; Clark T. Hung (Annals of Biomedical Engineering, 2007)

A multicopper oxidase is essential for manganese oxidation and laccase‐like activity in Pedomicrobium sp. ACM 3067 - Justin P. Ridge; Marianne Lin; Eloise I. Larsen; Mark Fegan; Alastair G. McEwan; Lindsay I. Sly (Environmental Microbiology, 2007)
Summary Pedomicrobium sp. ACM 3067 is a budding‐hyphal bacterium belonging to the α‐ Proteobacteria which is able to oxidize soluble Mn 2+ to insoluble manganese oxide. A cosmid, from a whole‐genome library, containing the putative genes responsible for manganese oxidation was identified and a primer‐walking approach yielded 4350 bp of novel sequence. Analysis of this sequence showed the presence of a predicted three‐gene operon, mox CBA. The mox A gene product showed homology to multicopper oxidases (MCOs) and contained the characteristic four copper‐binding motifs (A, B, C and D) common to MCOs. An insertion mutation of mox A showed that this gene was essential for both manganese oxidation and laccase‐like activity. The mox B gene product showed homology to a family of outer membrane proteins which are essential for Type I secretion in Gram‐negative bacteria. mox BA has not been observed in other manganese‐oxidizing bacteria but homologues were identified in the genomes of several bacteria including Sinorhizobium meliloti 1021 and Agrobacterium tumefaciens C58. These results suggest that mox BA and its homologues constitute a family of genes encoding an MCO and a predicted component of the Type I secretion system.

Analysis of extended HLA haplotypes in multiple sclerosis and narcolepsy families confirms a predisposing effect for the class I region in Tasmanian MS patients - Justin P. Rubio; Melanie Bahlo; Jim Stankovich; Rachel K. Burfoot; Laura J. Johnson; Stewart Huxtable; Helmut Butzkueven; Ling Lin; Bruce V. Taylor; Terence P. Speed; Trevor J. Kilpatrick; Emmanuel Mignot; et al. (Immunogenetics, 2007)

Cocaine increases human immunodeficiency virus type 1 neuroinvasion through remodeling brain microvascular endothelial cells - Milan Fiala; Amy J Eshleman; John Cashman; Justin Lin; Albert S Lossinsky; Vannina Suarez; Wendy Yang; Jun Zhang; Waldemar Popik; Elyse Singer; Francesco Chiappelli; Eva Carro; et al. (Journal of NeuroVirology, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)